Waiting to be found : papers on children in care - Briggs, Andrew, ....-; Rustin, Margaret, ....- (London : Karnac Books, 2012)
This book is about children in State care and its title – Waiting to be Found – is derived from an observation about such children by the child psychotherapist Hamish Canham. In one of his early papers Canham wrote that children's homes often reminded him of "station waiting rooms with children waiting to move on to their next placement and staff waiting for the next shift, or working as a residential social worker in order to get experience before moving on to do something else or further training.” This book takes his comment about waiting rooms as its starting point, with each contributor building upon its central implications. The contributors to this book each explore the importance of relationship; whether between child and care system, child and clinician or other practitioner, practitioners with practitioners, or individuals with the organisation in which they work. Overall they demonstrate when attention is paid to any one of these relationships this determines emotional-psycho-social success for the child, and how when this attention is missing serious issues arise. As a snapshot view of the way Canham's focus is used today they show that he was ahead of his time in thinking about the structure and function of what we now recognise as the corporate parent.
Includes bibliographical references (p. 295-308) and index.
Keywords: Child care; Child development; Child psychology; Children -- Institutional care; Jeugdpsychotherapie; Kinderpsychotherapie; Psychoanalyse; Residentiële jeugdzorg